Long-term echocardiographic evaluation of valvular lesions in a patient with nonbacterial thrombotic endocarditis associated with advanced uterine cancer. Issue 3 (September 2016) - Yokoyama, Shinobu; Iwano, Hiroyuki; Yamada, Satoshi; Takeda, Mahito; Kaga, Sanae; Nakabachi, Masahiro; Nishino, Hisao; Ichikawa, Ayako; Abe, Ayumu; Okada, Kazunori; Murai, Daisuke; Hayashi, Taichi; et al.
Abstract: Nonbacterial thrombotic endocarditis (NBTE) is characterized by the deposition of thrombi on previously undamaged heart valves in the absence of bacteremia and predominantly affects patients with hypercoagulable state. Although the diagnosis is usually based on transthoracic echocardiography, little is known about the serial changes of the vegetation in response to treatment. We experienced a 42-year-old woman with advanced uterine cancer and asymptomatic cerebral embolization. Plasmad -dimer level was markedly elevated and echocardiography showed highly mobile masses attached to the anterior and posterior mitral leaflets with moderate regurgitation. Based on these findings, she was diagnosed as having NBTE associated with uterine cancer and intravenous administration of heparin and chemotherapy were performed. Follow-up echocardiography revealed the disappearance of the vegetation and reduction of mitral regurgitation. Uterine cancer was successfully treated by surgery and recurrence of the valvular lesion did not occur. <Learning objective: Echocardiographic follow-up of valvular lesions could be a useful guide of the response to the treatment in patients with nonbacterial thrombotic endocarditis. Accordingly, anticoagulation therapy with careful follow-up echocardiography before the removal of the original cancer could be a reasonable approach in these patients.>